A new GaN-based converter design for electric vehicle charging system - Snehalika, Snehalika; Patel, Ranjeeta; Abhishek, Amruta; Panigrahi, Chinmoy Kumar; Pati, Ranjan Keshari (Institute of Advanced Engineering and Science, 2024)
The research work proposes a gallium nitride (GaN) based isolated bidirectional DC-DC (IBDC)-triple active bridge (TAB) based multi-port converter (MPC) for electric vehicle (EV) charging. The proposed GaN IBDC-TAB based MPC incorporates one input port (Port 1) and two output ports (Port 2 and Port 3) for charging, implying the use of fewer components compared to a conventional dual active bridge (DAB) charging system. The output ports can be operated individually in single active bridge (SAB), Dual active bridge (DAB), and TAB modes. A 12 kW GaN IBDC-TAB based MPC converter is designed for simulation study using LTspice XVII software. In the TAB mode of operation, output Port 2 designated for Level-1 (L-1) charging produces 1.5 kW, and output Port 3 designated for Level-2 (L-2) charging produces 10.6 kW. The maximum efficiency of 98.87% is obtained in simulation for the MPC converter in TAB mode. For experimental validation, a 0.91 kW prototype is presented with Port 1, Port 2, and Port 3 voltages as 230 V, 120 V, and 200 V respectively with the considered switching frequency of 100 kHz. The single-phase-shift control strategy is implemented for controlling the transmitted power in the proposed GaN IBDC-TAB converter.